Analysis of key factors for airport service quality: A case study of three regional airports in Thailand - Sarocha Kratudnak (2018)
© IEOM Society International. Airports open their doors to visitors and investors from around the world, crucially boosting the economy, trade, investment, and tourism of countries throughout the world. This paper aimed to categorize service quality factors used in the service evaluation of three regional airports in Thailand were used on case study. The factors of airport service quality were accumulated through literature review survey of service satisfaction from 300 passengers. Exploratory Factor Analysis (EFA) was then deployed and in a used to analyze the data from the survey to categorize into sub-factors. Analytic Hierarchy Process (AHP) was also used to evaluate the weight factors via pairwise comparison. Findings of this research provide the key factors of service quality for aviation authorities and airport administrators to raise service level in their respective airports.